2011
DOI: 10.1017/s0263034611000048
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation and growth of nanoparticles during pulsed laser deposition in an ambient gas

Abstract: We present a method to determine where the nanoparticles nucleate and grow during pulsed laser deposition in an ambient gas. Briefly, nanocrystalline Si films are systemically deposited on the substrates located at a distance from the plasma and placed in horizontal direction; meanwhile an external electric field is introduced perpendicularly to the plume. Based on the transportation dynamics of Si nanoparticles corresponding to different electric fields, the lateral nucleation range of 0.1 to 33.8 mm is deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 40 publications
(46 reference statements)
0
13
0
Order By: Relevance
“…The mechanisms for nucleation and growth process have been discussed, in detail,elsewhere. [31,32] Reinholdt et al showed that irradiatingapressed TiNp owder target with aN d:YAGl aser formed cuboid-shaped particlesb yu sing transmission electron microscopy (TEM) ( Figure 2A). [33] The particles were crystalline and below 10 nm in size, with ar elativelyb road size distribution.…”
Section: Laser Ablationmentioning
confidence: 99%
“…The mechanisms for nucleation and growth process have been discussed, in detail,elsewhere. [31,32] Reinholdt et al showed that irradiatingapressed TiNp owder target with aN d:YAGl aser formed cuboid-shaped particlesb yu sing transmission electron microscopy (TEM) ( Figure 2A). [33] The particles were crystalline and below 10 nm in size, with ar elativelyb road size distribution.…”
Section: Laser Ablationmentioning
confidence: 99%
“…The density and velocity distributions are obtained and the formation mechanism of the velocity splitting is also analyzed [11] . The pressure, however, is much higher than that in most of the experiments [12,13] , and the formation mechanism of the two splitting cycles was not distinguished. The gas pressure is a key parameter which influences the ablated-particle density and velocity distributions, and the structural properties of the nanoparticles [14,15] .…”
Section: Introductionmentioning
confidence: 69%
“…34,35 Pulsed laser deposition (PLD) in the presence of a buffer gas has been reported as a versatile tool for fabricating nanoparticles and other nanostructures with controlled size. [36][37][38] This technique is used to synthesize MO electrodes as well. [39][40][41][42] Yang synthesized MOs using manganese metallic and Mn 3 O 4 targets in an O 2 atmosphere with pressures ranging from 1 mTorr to 0.5 Torr and obtained crystalline phases of Mn 2 O 3 , Mn 3 O 4 and amorphous MnO x .…”
Section: Introductionmentioning
confidence: 99%